3
$\begingroup$

I used the power rule and the chain rule and ended up with this: $$y'= (3x-1)^2 \times 2(2x+3) \times 2 + (2x+3)^2 \times 2(3x-1)\times 3$$

The next step, which I do not understand how it is combined or created is this:

$$y'= 2(3x-1)(2x+3)\left[2\cdot(3x-1)+3(2x+3)\right]$$ Where did the exponents go? What is combined? How is it combined?

The Final Answer should be this, according to my teacher: $$y'= 2(3x-1)(2x+3)(12x+18)$$

$\endgroup$
2
  • $\begingroup$ No it's all correct. $\endgroup$
    – Britney
    Sep 30, 2014 at 6:44
  • 1
    $\begingroup$ @Nick Assuming the OP copied the expected answer correctly, your edit is fine; it's just that the teacher's answer is incorrect. (The $18$ should be a $7$.) Three of us + Maple (I checked) have come up with the correct answer. :-) $\endgroup$
    – James
    Sep 30, 2014 at 6:51

2 Answers 2

1
$\begingroup$

I think that you forgot that the derivative of $u^n(x)=n u^{n-1}(x)u'(x)$.

I suppose that you want the derivative of $$y=(3x-1)^2 (2x+3)^2$$ So, let us set $u=(3x-1)^2$ and $v=(2x+3)^2$. So $y=u\times v$ and $y'=u'\times v+u\times v'$.

Now $$u'=2\times(3x-1)'\times(3x-1)=6(3x-1)$$ $$v'=2\times(2x+3)'\times(2x+3)=4(2x+3)$$ $$u'\times v+u\times v'=6(3x-1)(2x+3)^2+4(2x+3)(3x-1)^2$$ Factor $(3x-1)(2x+3)$; so $$u'\times v+u\times v'=(3x-1)(2x+3)\Big(6(2x+3)+4(3x-1)\Big)$$ Expand what is inside the last bracket and simplify to arrive to $$y'=2 (2 x+3) (3 x-1) (12 x+7)$$

With reference to the exponents, look at the first line and think about $n=2$ and remember that we never use exponent $1$ in such context of polynomials.

$\endgroup$
2
  • $\begingroup$ Oh! Thank you so much, I didn't realize she factored it out. And yes, my math teacher makes a lot of mistakes so it wouldn't be unusual for the answer to be different. $\endgroup$
    – Britney
    Sep 30, 2014 at 6:53
  • $\begingroup$ You are very welcome. When you have powers such as in $y=u^n \times v^m$, the common factor will be $u^{n-1}\times v^{m-1}$. Just for fun, prove it. Cheers :-) $\endgroup$ Sep 30, 2014 at 6:58
0
$\begingroup$

$$(f^2g^2)'=((fg)^2)'=(h^2)'=2h'h=2(f'g+fg')fg$$

$$\Big((3x-1)^2(2x+3)^2\Big)'=2\Big(3(2x+3)+(3x-1)2\Big)(3x-1)(2x+3)=2(12x+7)(3x-1)(2x+3)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.